A current control method for bidirectional multiphase DC-DC boost-buck converter - Gifari Iswandi Hasyim; Sulistyo Wijanarko; Jihad Furqani; Arwindra Rizqiawan; Pekik Argo Dahono (International Journal of Electrical and Computer Engineering (IJECE), 2022)
In the future, more and more electric vehicle (EV) batteries are connected to the direct current (DC) microgrid. Depending on the battery state of charge, the battery voltage can be higher or lower than the DC microgrid voltage. A converter that is aimed to fulfil such function must be capable of working in both charging and discharging regardless the voltage level of the battery and DC microgrid. Battery performance degradation due to ripple current entering the battery is also a concern. In this paper, a converter that can minimize ripple current that entering battery and operate in two power-flow directions regardless of battery and DC microgrid voltage level is presented. A current control method for this kind of converter was proposed. Experiment on a prototype was conducted to prove the proposed converter current control method.